Analisis Keseimbangan Lintasan pada Lantai Produksi CV. Bobo Bakery - Merry Siska; Ruby Suryanata (UIN Sultan Syarif Kasim Riau, 2012)
An industry always expected to operate more efficiently in order to still be able to compete with other industries. One effort efficiency to do is to minimize the number of work stations, especially on the assembly work station path balancing method of production used the method ranked positional weight (RPW). The observations made in the data collection as much as 20 times each station observed and calculated test the adequacy and uniformity of data that can be obtained by standard time. From the data processing method RPW shows increased production efficiency is 35% at the starting position and following a path balancing the production efficiency of up to 83% due to, among others, the incorporation of several work stations where the initial conditions account for 7 stations and after the merger becomes 3 work stations, while initial jobless 2.97 to 0.33 this means that there is a decrease of 2.64 minutes. Initial wait time balance 64.28% to 16.6%, this means that there is a decrease of 47.68%. The balance of the track on the floor CV. Bobo's Bakery requires improved methods of work, laying machines with operators who have good skills in order to facilitate the operator's work in order to obtain the balance of the production trajectory.Keywords: Line Balancing, Wait Time,Eficiency